Stability of grain and fodder yields in extra-early cowpea genotypes in Southeastern Niger - Souleymane Abdou; Abdoul Moumouni Iro Sodo (PLoS ONE, 2026)
Cowpea [ Vigna unguiculata (L.) Walp.] is a vital food and fodder crop in Niger, but its productivity is constrained by drought, poor soils, striga and pest pressures. Developing extra-early dual-purpose varieties is essential for strengthening food and feed security in these fragile production zones. This study evaluated the effects of genotype, environment, and their interaction on the stability of grain and fodder yields in 21 cowpea genotypes tested across six environments using an alpha-lattice design with three replications. Stability was assessed through Shukla’s stability variance, the cultivar superiority index, Wricke’s ecovalence, GGE biplot, and the multi-trait genotype–ideotype distance index (MGIDI). Results revealed significant differences among genotypes, environments, and genotype × environment interactions for all traits; environmental effects had the highest mean squares for all traits (p < 0.001). Broad-sense heritability ranged from 0.77 (fodder yield) to 0.88 (days to 50% flowering), and genetic advance as percentage of mean was high for yield traits (GAM = 78.67% for pod yield, 81.80% for grain yield, 99.59% for fodder yield), indicating strong selection potential. Mean grain yield across all genotypes and environments was 1,394.32 kg ha ⁻ ¹, and the coefficient of variation ranged from 26.59% (GY) to 40.63% (FY). Notably, ten extra-early lines—BM22, BP02, BP15, MM142, 65B5080, BP18, BM21, BM13, MM141, and BM12—were identified as combining early maturity with high and stable grain and fodder yields. These lines should be further evaluated across diverse agroecological zones to confirm their adaptability and alignment with farmer preferences, prior to deployment as released varieties or as parents in cowpea improvement programs targeting climate-resilient, dual-purpose productivity in the Sahel.